Konstrukce předpjaté budovy Národní technické knihovny v Praze - Salcedo Salinas, Fiorella Silvana; Salcedo Salinas Fiorella Silvana (České vysoké učení technické v Praze, 2017)
V rámci práce byl zadán půdorys typického patra Národní technické knihovny

In this thesis, the concrete layout of the National Technical Library (Annex #) was given in order to develop a solution for the structural design of the slab. The architectural layout of slab was visually analyzed to understand its complexity. Next, the model of the structure in the finite element software SCIA Engineer was done to evaluate more in depth the structural behavior of the slab against the imposed loadings. Three models were prepared before obtaining one that could show proper results. For the first model, some interesting features of the software were used to model the structure as similar as possible to the real one but the model was not working, thus, the model was simplified. With this results the possibility of using conventional concrete for the design of this slab was assessed. The main indicator used for this purpose was the long-term deflection of the slab, which resulted more that the permitted limit. As expected, the solution of the structure with conventional reinforced concrete was not possible. Therefore, it was decided to use pre-stressed concrete to reinforce the structure given the characteristics of the architecture. The method used for the design and modeling was the load balancing method. The pre-stressed reinforcement was designed to balance 80% of the dead load and then modeled in SCIA Engineer. Finally, the results were checked in the Ultimate limit state and the Serviceability limit state.
Prestressed building of the National Technical Library in Prague
Keywords: Předpjatá stavba, návrh a kontrola, základní betonové detaily.; Prestressed building, design and check, basic concrete details.